2020 19th IEEE International Conference on Machine Learning and Applications (ICMLA) 2020
DOI: 10.1109/icmla51294.2020.00075
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Covert Attack Identification for Industrial Control Systems

Abstract: Cybersecurity of Industrial Control Systems (ICS) is drawing significant concerns as data communication increasingly leverages wireless networks. A lot of data-driven methods were developed for detecting cyberattacks, but few are focused on distinguishing them from equipment faults. In this paper, we develop a data-driven framework that can be used to detect, diagnose, and localize a type of cyberattack called covert attacks on smart grids. The framework has a hybrid design that combines an autoencoder, a recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Li et al [ 14 ] analyzed the sensor data of the wind turbine with professional knowledge and, after feature extraction, uses the hyperparameter search method to train the support vector machine model to diagnose faults. Finally, Yokouchi and Kondo [ 15 ] introduced a single-class SVM model to learn the boundary of the common data space by collecting the equipment's average data and applying it to the fault detection of the equipment.…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [ 14 ] analyzed the sensor data of the wind turbine with professional knowledge and, after feature extraction, uses the hyperparameter search method to train the support vector machine model to diagnose faults. Finally, Yokouchi and Kondo [ 15 ] introduced a single-class SVM model to learn the boundary of the common data space by collecting the equipment's average data and applying it to the fault detection of the equipment.…”
Section: Related Workmentioning
confidence: 99%
“…From the loss versus epoch variation, it worth saying that the convergence of the model was reached in the first ten iterations, which may lead to serious overfitting problems [113]. In [114], a cybersecurity diagnosis and localization method using hybridization of AE, RNN, LSTM, and DNN has been proposed. Despite the model's universality potential to cope with other networked industrial control systems, it has been found that this hybrid design can not detect unknown attack/fault types [114].…”
Section: H Hybrid Models-basedmentioning
confidence: 99%
“…In [114], a cybersecurity diagnosis and localization method using hybridization of AE, RNN, LSTM, and DNN has been proposed. Despite the model's universality potential to cope with other networked industrial control systems, it has been found that this hybrid design can not detect unknown attack/fault types [114]. A novel Graph Neural Network (GNN) based framework, combining graph convolutional network (GCN) and LSTM model has been proposed for multi-task multi-task transient stability classification [115].…”
Section: H Hybrid Models-basedmentioning
confidence: 99%
“…Furthermore, the proposed wireless interference level estimation is a general approach that can be applied in different industrial use cases. The approach follows the idea of using a data-driven anomaly detection and estimation approach in industrial control systems [11]. In this approach, a system model is trained for the industrial use case, while performing 5 ______________________________________________________________________________________________________ under different conditions, using a machine learning technique.…”
Section: Introductionmentioning
confidence: 99%